PENINGKATAN HASIL BELAJAR MATEMATIKA DENGAN MENGGUNAKAN ALAT PERAGA PADA SISWA KELAS II DI SDN 013 RAMBAH - Liswati Liswati (JURNAL PENDIDIKAN ROKANIA, 2019)
This study aims to improve mathematics learning outcomes in grade II students at SDN 013 Rambah. This type of research is classroom action research or action research. The results obtained from this study, By providing intensive guidance to students, especially when students experience learning difficulties, students' mastery of mastery classically increased from the first cycle there were 23 students who reached KKM with a percentage of completeness 82.1% and those who did not reaching KKM of 5 students with a percentage of 17.8%. Classically learning outcomes have not been declared complete. In the second cycle the learning outcomes increased there were 26 students who reached KKM with a percentage of completeness 92.9% and those who did not achieve KKM were 2 people with a percentage of 7.1% classically the student learning outcomes were complete.